Social Medicine and Bioethics (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This article analyzes the role of bioethics within the context of social medicine and public health, with a particular focus on the social determinants of health, as framed within the bio-psycho-social model of health and illness. Special attention is given to situational vulnerability and inequities in access to healthcare. The analysis also considers behavioral and environmental determinants, as they relate to social determinants, and highlights the necessary transformations in public policy, especially regarding the need for health literacy and education.
Keywords: bioethics; social determinants of health; situational vulnerability; health inequities; health literacy and education